2020
DOI: 10.1167/iovs.61.11.40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrical Stimulation of Cervical Sympathetic Ganglia on Intraocular Pressure Regulation According to Different Circadian Rhythms in Rats

Abstract: The purpose of this study was to investigate the relationship between circadian rhythm and intraocular pressure (IOP), and to explore whether electrical stimulation of cervical sympathetic ganglia (SCG) can regulate IOP via neurotransmitter distribution around the Schlemm's canal (SC) in rats. METHODS. Sprague Dawley rats were housed under normal (N-normal), constant dark (N-dark), and constant light (N-light) rhythms (n = 6 per group). Electrical stimulation (intermittent wave [20 hertz {Hz}, 2 mA, 10 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The eye presumably must remain connected to circulatory and neural signals from the suprachiasmatic nucleus, which has been shown to regulate IOP rhythmicity [ 33 , 34 ]. Observed changes in outflow resistance may reflect sympathetic shrinkage of Schlemm’s canal [ 35 ], suppression of trabecular meshwork phagocytosis [ 36 ], or other processes under circadian control.…”
Section: Discussionmentioning
confidence: 99%
“…The eye presumably must remain connected to circulatory and neural signals from the suprachiasmatic nucleus, which has been shown to regulate IOP rhythmicity [ 33 , 34 ]. Observed changes in outflow resistance may reflect sympathetic shrinkage of Schlemm’s canal [ 35 ], suppression of trabecular meshwork phagocytosis [ 36 ], or other processes under circadian control.…”
Section: Discussionmentioning
confidence: 99%
“… 61 63 The diameter of Schlemm's canal is reduced when the superior cervical ganglion is stimulated, followed by a rise in IOP, suggesting that local sympathetic stimulation can increase IOP. 64 66 Nocturnal IOP is lower, which correlates with a decreased sympathetic tone. 67 Clinically, drugs of sympathetic inhibition are used to treat glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…NOS in the endothelium mediates pressure-dependent drainage, which may form a negative feedback pathway [ 197 ]. A previous study has suggested that under electric stimulation of SCG in rats, the expression of DβH in the SC endothelium is increased, and the cross-sectional area and perimeter of the SC are reduced [ 198 ]. This may explain the elevated IOP [ 199 ].…”
Section: Physiological Effectmentioning
confidence: 99%